Knowledge and perception of HPV vaccination among Lebanese mothers of children between nine and 17 years old - Nassif Elissa; Hadchity Charbel; Azzi Marly; Nader Ingrid; Saleh Nadine; Abdo Rachel (BMC, 2024)
Abstract Background The human papillomavirus (HPV), a prevalent sexually transmitted infection, is linked to a wide range of diseases, with cervical cancer being the most common and serious one. HPV vaccination is crucial for preventing cervical cancer and other HPV-related problems. The low acceptability of HPV vaccination among teenagers globally is largely due to a lack of understanding and information about HPV among parents. Our study aimed to evaluate the level of knowledge, attitude, intention, and HPV vaccination among parents in Lebanon as well as the variables influencing Lebanese mothers' intentions to vaccinate their children. Methods A cross-sectional survey-based study involving 392 participants was conducted between May and June 2022. The study assessed parents' intention to vaccinate their children against HPV, their knowledge about HPV, and the HPV vaccine. The data was collected through an anonymous electronic questionnaire. A bivariate analysis was conducted using Student t-test and ANOVA to examine the relationship between the dependent variable "Intention to vaccination" and the secondary variables. The level of statistical significance was set at 0.05 for all data. Results Our findings showed that only 63% of the 392 participants claimed they would give their child the HPV vaccination. A positive significant association was demonstrated between "Intention to vaccinate against HPV" and mother's nationality, father's educational level, family income per month, information received about the HPV vaccine, parents' HPV vaccination, insurance coverage of the HPV vaccine, children's vaccinations with all required vaccines, knowledge of HPV, and knowledge of the HPV vaccine. Furthermore, when parents know about HPV, their desire to vaccinate their child increases by a factor of 1.832 times, and by 1.207 times when their knowledge level increases by one point. Conclusion The majority of parents lacked a general understanding of most HPV-related statements, which highlights the requirement for educational interventions to raise parental awareness, understanding, and attitudes toward HPV and, as a result, increase parental acceptance of vaccinating their children. To increase the vaccination rate among adolescents, government authorities should ensure that the HPV vaccine is available in all hospitals and clinics and should be provided free of charge.